Facile synthesis of microwave-etched Ti3C2 MXene/activated carbon hybrid for lithium-ion battery anode - Muhammad Amirul, Aizat Mohd Abdah *; Jayesh, Cherusseri *; Nurul Akmaliah, Dzulkarnain; Marliyana, Mokhtar; Mohd Sukor, Su'ait; Tan, Yee Seng *; Muhammad Norhaffis, Mustafa *; Mohammad, Khalid *; Arshid, Numan *; Amr, Radwan * (Elsevier, 2023)
In this study, we synthesized MXene hybrid electrodes using a novel strategy to generate a synergistic effect between the respective components. Initially, a few-layered Ti3C2 MXene was prepared via microwave-assisted in-situ etching. The AC to Ti3C2 MXene ratio is varied to be 10:0, 9:1, 8:2, and 7:3 in order to maximize electrochemical efficiency. As an anode material for LIBs, the hybrid AC_Ti3C2 (8:2) electrode exhibits the highest initial specific capacity of 1194.2 mAh/g discharged at a current density of 0.2 A/g and maintains over 841.8 mAh/g after 80 consecutive cycles (with a Coulombic efficiency of ∼100 %). An increase in the discharge capacity of the hybrid electrode from 750.5 to 881.9 mAh/g when the current density changed from 1 to 0.2 A/g suggests the excellent rate capability of the AC_Ti3C2 (8:2) hybrid electrode. Furthermore, electrochemical impedance spectroscopic analysis of AC_Ti3C2 (8:2) shows a low charge transfer resistance (Rct) of 8.52 Ω, indicating good conductivity of the hybrid electrode. The work presented here confirms that the AC can be used as an interlayer spacer in synthesizing Ti3C2 MXene hybrids and have excellent application prospects for the next-generation LIBs.